An Analysis of the Factors that Affect International Student Choice of Higher Education Institution Based “One Belt One Road” Policy - Zhang Bei; Rashad Yazdanifard (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
The aim of this study is to investigate the factors through which international students choose higher education institutions (HEIs) in Shaanxi Province in China. It focuses on the variables that influenced international students’ decision to choose HEIs in Shaanxi, China as their educational location. A questionnaire with 44 questions was developed and distributed to 714 students. Out of these 714 students, only 500 questionnaires were returned. The data analysis was conducted using the micro, meso, and macro factors highlighted in the conceptual framework. At various levels, the effect of the various independent variables on the decision of international students to study in Shaanxi province was evaluated. The results indicates that international experience of the university, language practiced by the university & , admissions policy adopted by the university has an impact on International Students’ Choice of Study in Shaanxi Province. It is also important for international market positioning and enhancing the capabilities of higher education institutions.